KAJIAN AKAD PEMBIAYAAN LOGAM MULIA UNTUK MASYARAKAT PADA PEGADAIAN SYARIAH - Irayana Harpen (Lembaga penelitian dan pengabdian kepada masyrakat, 2014)
Pawn Shari'ah or rahn at first is one of the products offered by Islamic Bank . Bank Muamalat Indonesia (BMI) as the first Islamic bank in Indonesia has entered into a collaboration with Pawnshop , and gave birth to Sharia Pledge Service Unit (now, Pawnshop Branch Sharia ) which is an independent institution based on Islamic principles . One of the products on offer is the sharia mortgage financing MULIA ( Murabaha Precious Metals Investing For Eternal ) . From the observation of the writer , Implementation murabaha contract and financing agreement MULIA Rahn in accordance rukunnya terms and according to Islamic law , both involving al - ' Akid ( the parties ) , al - ma'kud ' alaih (object agreement ) or sighat ( consent and granted ) . MULIA with murabaha financing and rahn contract does not include the two covenants in a prohibited transaction , because the murabaha contract as the contract agreement was essentially rahn ( pledge ) is asessoir . Barriers to implementation of the agreement MULIA murabaha financing and rahn on Pawn Sharia are the following factors : first , the presence of factor legal opinion that most people murabaha financing agreement and MULIA with rahn contract is included in the category of